Pathobiology of Multidrug Resistant Acinetobacter baumannii: An update - Kumar, Sunil; Yadav, Mukesh; Sehrawat, Nirmala; R, Rakesh; Alrehaili, Jihad; Anwer, Razique (Asian Journal of Biological and Life Sciences)
Acinetobacter baumannii is an opportunistic nosocomial pathogen responsible for mortality and mobidity asscoaited with hospital acquired infections worldwide. Antimicrobial resistance due to natural and acquired modes facilitates A. baumannii as one of the most significant nosocomial pathogens. Challenging most issue is the carbapenem resistance in A. baumannii in the healthcare settings worldwide, which is conferred by several mechanisms including: beta-lactamases, reduced permeability of the outer membrane, efflux pumps, and modification of penicillinbinding proteins. Among these, carbapenem-hydrolysing enzymes are the foremost mechanism that belongs to Ambler class D and B beta-lactamases. Several techniques are used to study the molecular epidemiology like WGS, PFGE, MLST, RFLP and RAPD. Among these, MLST is the gold standard, which are prevalently used to study the evolutionary geentics and clonal relatedness of A. baumannii clones. A. baumannii has been investigated in a number of outbreaks in clinical settings and spread of infections in hospital environments. To enhance our knowledge, in this review, we study the taxonomy, lab diagnosis, molecular techniques of identification, mechanisms of its antimicrobial resistance, molecular epidemiology and outbreaks, bacterial cell firness and use of animal models in multidrug resistant (MDR) A. baumannii.
Keywords: Acinetobacter baumannii; Antimicrobial resistance; Molecular Epidemiology; Outbreaks; Virulence Factors